2016
DOI: 10.1016/j.envres.2016.06.041
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of As accumulation under different pH levels: Comparing Ruditapes decussatus and Ruditapes philippinarum biochemical performance

Abstract: Marine bivalves have been used to assess environmental As contamination and the effects of seawater acidification when both factors are acting alone, but limited information is available regarding the impacts of both factors acting in combination. The aim of this study was to compare physiological (glycogen) and biochemical (lipid peroxidation, superoxide dismutase, catalase, glutathione-S-transferase and alkaline phosphatase) responses in both native (Ruditapes decussatus) and introduced (R. philippinarum) cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 85 publications
2
6
0
Order By: Relevance
“…diversicolor usually increased when exposed to contaminants, such as mercury [ 75 ]. The same pattern was observed with Diopatra neapolitana when exposed to arsenic and to metals and As [ 22 , 24 ] and with the bivalve Ruditapes philippinarum exposed to As [ 101 ].…”
Section: Discussionsupporting
confidence: 65%
“…diversicolor usually increased when exposed to contaminants, such as mercury [ 75 ]. The same pattern was observed with Diopatra neapolitana when exposed to arsenic and to metals and As [ 22 , 24 ] and with the bivalve Ruditapes philippinarum exposed to As [ 101 ].…”
Section: Discussionsupporting
confidence: 65%
“…Although the manila clam consistently revealed higher LPO levels and the European clam presented higher levels of PC in the whole tissue, this characteristic could be a reflection of their natural biochemical composition and not a deleterious sign since oxidised by-products formation was not induced by exposure to TCS alone or combined with physical stressors. Moreover, in accordance to a higher antioxidant pool (CAT, GPx and GSTs activities) in R. decussatus, LPO levels were consistently lower in this species as formerly pointed out (Costa et al, 2020;Velez et al, 2016c). However, remarkable higher PC values were observed in the native clam at both scenarios, despite the total PROT content did not follow this species trend.…”
Section: Oxidative Stress Damage Measuressupporting
confidence: 63%
“…peroxidation (LPO)) and neurotoxicity (e.g., acetylcholinesterase (AChE)) (Bebianno et al, 2004). While several studies showed that these biochemical markers are useful in detecting possible damages under metal pollution (Velez et al, 2016;Wang et al, 2011;Yesudhason et al, 2013;Gomes et al, 2013) eutrophication (Verdelhos et al, 2005) and pharmaceuticals (Freitas et al, 2015;Antunes et al, 2013;Matozzo et al, 2016b;Correia et al, 2016), less is known on the biochemical alterations induced by CNMs in this group of organisms (Cattaneo et al, 2009;De Marchi et al, 2017a;Canesi and Corsi, 2015;Miller et al, 2015;Matranga and Corsi, 2012;De Marchi et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%